2018
DOI: 10.4103/ams.ams_224_18
|View full text |Cite
|
Sign up to set email alerts
|

Considerations regarding dental implant surfaces, bone reaction and “Peri-implantitis”

Abstract: This article explains, based on a long-term observation, the hard-tissue reaction to different endosseous implant surfaces and different implant designs. A patient who had received a full maxillary implant-supported restoration on basal implants and compression screws followed by immediate loading presented no clinical problems at the 20-year follow-up, but the X-ray examination revealed different hard tissue reactions to different implant types. No bone loss was found around lateral basal implants with fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…61 Bone strength is directly related to bone density 62 as bone material density (BMD) 63 is used to determine the risk of fracture of bone and, indirectly, the stress shielding effect 33 in the bone. Considering the geometrical conditions of the basal dental implants 18,19 compressive load of 200 N 33 applied on the top surface of the implant, and maximum von Mises stress are observed at the implant neck, 64 followed by the shaft of the implant which is similar to the previous study done on the dental implant. 19 Von Mises strain analysis (Figure 7) is performed for the bone-implant assembly for normal, hard, and soft bone conditions.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…61 Bone strength is directly related to bone density 62 as bone material density (BMD) 63 is used to determine the risk of fracture of bone and, indirectly, the stress shielding effect 33 in the bone. Considering the geometrical conditions of the basal dental implants 18,19 compressive load of 200 N 33 applied on the top surface of the implant, and maximum von Mises stress are observed at the implant neck, 64 followed by the shaft of the implant which is similar to the previous study done on the dental implant. 19 Von Mises strain analysis (Figure 7) is performed for the bone-implant assembly for normal, hard, and soft bone conditions.…”
Section: Resultssupporting
confidence: 83%
“…13 Finite element analyses 14 are used for determining the stress and load-bearing capacity on the dental bone, and it is observed that penurious transfer of load, misplacement of the dental implant, 15 improper geometry of implant, 16 primary and secondary stability of implant 17 are some of the factors that affect implant failure. As a result, patient-specific bone-friendly 18 dental implants are designed which include multiple design variables 19 like diameter, length of the implant, 20 supply of blood to tissues, 21 the primary stability, 22 mobility, 23 and quality of bone 24 that are checked at the time of placement of the implant. It is well-known that lot of care should be taken while placing the dental implant in the basal bone.…”
Section: Introductionmentioning
confidence: 99%
“…If lateral basal implants with sandblasted shaft are used, crater-like bone loss is observed after a number of years. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…Compared to all these interventions, our treatment seems almost minimally invasive, almost painless; the patients recover fast, and the result is highly predictable. [ 20 21 22 ]…”
Section: Discussionmentioning
confidence: 99%